Correcting the Record: Haida Oral Tradition in Anthropological Narratives - Sparrow, Kathy Bedard (Anthropologica, 2022)
For over 100 years, anthropological and popular sources have perpetuated Rev. Charles Harrison's published account of Haida chief Albert Edward Edenshaw and the corroborating accounts of Edenshaw's descendants. These sources have misrepresented Edenshaw, and here I present Haida oral traditions which dispute Edenshaw's claim to be the "greatest of all Haida chiefs." This case study points to problems of his torical reconstruction which rely on too few sources and an external frame of reference